Mycobacterium tuberculosis Rv1265 promotes mycobacterial intracellular survival and alters cytokine profile of the infected macrophage. Issue 3 (3rd March 2016) - Luo, Hongping; Zeng, Jie; Huang, Qinqin; Liu, Minqiang; Abdalla, Abualgasim Elgaili; Xie, Longxiang; Wang, Huan; Xie, Jianping
Abstract : Mycobacterium tuberculosis cAMP and underlying regulatory network are crucial for its survival and thrive in the presence of numerous stresses mounted by the host . Our studies mainly focus on the cAMP-induced M. tuberculosis gene Rv1265, which was shown to be up-regulated under hypoxia and during macrophage infection by addition of exogenous cAMP. To explore the role of Rv1265 in host–pathogen interactions, Rv1265 was expressed in a non-pathogenic Mycobacterium smegmatis . We found that Rv1265 was associated with cell envelope and can up-regulate some cell wall fatty acid components, especially the C26:0. The survival of the recombinant Ms_Rv1265 was enhanced within macrophages and under stress conditions such as low pH and SDS. Macrophages infected with Ms_Rv1265 increased transcription of pro-inflammatory cytokines IL-1β, IL-6, and IL-12 P40 and anti-inflammatory cytokine IL-10 possibly through activation of NF-κB and ERK1/2 pathway. Our findings indicate that Rv1265 can enhance mycobacterial survival within macrophages, and perturb the cytokine profile of macrophage.